2011
DOI: 10.1021/ie201298x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Permeation through U-Shaped K2NiF4-Type Oxide Hollow-Fiber Membranes

Abstract: The first oxygen permeation data for a dense hollow-fiber membrane based on a K 2 NiF 4 -type oxide are reported. The U-shaped (Pr 0.9 La 0.1 ) 2 (Ni 0.74 Cu 0.21 Ga 0.05 )O 4+δ (PLNCG) hollow-fiber membranes were prepared by a phase-inversion spinning process. The dependences of the oxygen permeation on the feed air flow rate, sweep helium flow rate, oxygen partial pressure on the shell side, and operating temperature were experimentally investigated. The effects of the bulk diffusion and the surface exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…To change the driving force (oxygen concentration gradient between the two membrane sides), the oxygen partial pressure can be increased or decreased in the feed side or sweep the side, respectively. The latter mode is more conveniently operated in a laboratory just by adjusting the sweep gas flow rates as reported in earlier studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To change the driving force (oxygen concentration gradient between the two membrane sides), the oxygen partial pressure can be increased or decreased in the feed side or sweep the side, respectively. The latter mode is more conveniently operated in a laboratory just by adjusting the sweep gas flow rates as reported in earlier studies …”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the effects of sintering on the membrane microstructures and oxygen permeation behavior, the apparent activation energy was calculated from the various flux values at different operation temperatures by applying the Arrhenius plot (Figure b and S7, Supporting Information) . Comparing the average activation energy of M1400 (79.1 ± 1.5 kJ mol –1 ) with that of M1350 (112.0 ± 4.3 kJ mol –1 ), it can be observed that the former has a rather lower apparent activation energy, resulting from the difference in the sintering temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed ionic‐electronic conductors (MIECs) exhibit simultaneously high ionic and electronic conductivities. Perovskite and Ruddlesden–Popper oxide‐based MIECs in particular are among the best materials for oxygen separation membrane . Perovskite oxide provides isotropic oxygen ionic transport pathway given its cubic structure whereas Ruddlesden–Popper oxide exhibits anisotropic oxygen ionic transport pathway that favors transport in a certain direction.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen transport through the dense membranes made of these oxides normally occurs via oxygen ionic diffusion driven by the oxygen partial pressure gradient at high temperature (above 700°C) so that the passages of all other gas molecules are not allowed; thus giving them absolute oxygen selectivity. Previous studies have revealed that both perovskite and Ruddlesden–Popper oxides exhibit high oxygen permeability and structure stability …”
Section: Introductionmentioning
confidence: 99%